Experiencias de la práctica conjunta de estudiantes de higiene oral de la Universidad del Valle en los servicios de salud con comunidades de los municipios de Yumbo y Cali - Pérez Flores, Yolanda (Revista Estomatología, 2000)
The goal of this study is to let know the experience from the cornmunity practice carried on by 23 students of the oral hygienic program at the school of Dentistry at the University of the Valley, from August to December 1999. The purpose was to elaborate and develop a program of oral hygiene according to the regulations and policies established by the Ministry ofHea1th to undertake educational actions on oral cornmon diseases encouraging people to acquire good nutrional and oral habits to keep in good hea1th. The underlying principIes of the habits were: whole attention in the preventive aspects and interinstitutional coordination where resources from the official areas were channeled - University of the Valley, Health and Education offices and private institutions- and the community participation of the different social groups. Results from the activities performed are presented and suggestions to revise, improve the strategies for group work were outlined.